Fascicular pseudomelanoma. Clinical and dermoscopic findings. - Bonifazi, E.; Milano, A.; Ciampo, L. (European Journal of Pediatric Dermatology, 2004)
Pseudomelanoma, namely the reappearance of melanic pigmentation after removal of a nevus, is very frequent after removal of congenital melanocytic nevi, even in case of apparently radical removal. Here is reported the case of a child with giant congenital melanocytic nevus. After its removal the child presented a characteristic linear pseudomelanoma, perpendicular to the longitudinal axis of the scar, with dermoscopic parallel bundles, vaguely reminiscent of acral pigmented nevi.